(3cJGH ajg COdI GdePgH (B( (3ePgH eGdc Hf GfS(B) (3QVi Gddg Yfg ef GdbQBf hGdSfIs - (3CHh YHO GdQMef GdeQHYj GdeGdcj,J (B939 (3g` s ((3YHO Gddg Hf Ydi GdeGdci s)
(3ChdgG (B:s
(3GdOdjd Ydi Cf GdWgGQI ef GdMOK aQjVI bhdg JYGdi (B:( (3jG CjgG GdPjf BefhG EPG beJe Edi GdUdGI aGZSdhG hLhgce (B) (3Edi bhdg (B: ( (3Edi GdcYHjf (B) s
(3BNQgG (B:s
(3hdcfg Pdc GdSOS aGf GLJeYfG agh Hjfce hGjceG GfaQOJ NdJ Hg agh dgG LedI GdCOdI efGdbQGf hef GdSfI HMeO Gddg hYhfg s
(3cJHJ HQSe GdSjO GSeGYjd Hf Ydi Hf eMSf GdTQja GdMSfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(3134(3H(B) s
Keywords: (3Gdabg GdeGdcjs